THEORETICAL ANALYSIS OF THE PHENOMENON OF LEADERSHIP IN THE AGE OF VUCA - D. Veselovskiy; L. Mosina (Вестник университета)
The importance of studying leadership in uncertain conditions from the standpoint of an interdisciplinary approach is substantiated. The definition of VUCA is given. The features of modern socio-economic conditions are presented. Psychological characteristics of the leader’s behavior in unstable conditions are considered. The results of research of leadership phenomenon in uncertain conditions are presented. Dangers for the organization and possibilities of behavior of the leader in unstable conditions are considered. The importance of studying the category «leadership as a way of life» in the era of VUCA is substantiated. The prospects for further study of the phenomenon of leadership are determined.